To solve the system of equations:
- \( 4h + 4s = 10 \)
- \( 7h + 5s = 15 \)
We can start by simplifying the first equation. Dividing everything by 4:
\[ h + s = 2.5 \quad \text{(Equation 1)} \]
Now, we can express \( s \) in terms of \( h \):
\[ s = 2.5 - h \quad \text{(Equation 2)} \]
Next, we substitute Equation 2 into the second equation:
\[ 7h + 5(2.5 - h) = 15 \]
Distributing the 5:
\[ 7h + 12.5 - 5h = 15 \]
Combine like terms:
\[ 2h + 12.5 = 15 \]
Subtract 12.5 from both sides:
\[ 2h = 2.5 \]
Divide by 2:
\[ h = 1.25 \]
Now we can find \( s \) by substituting \( h \) back into Equation 2:
\[ s = 2.5 - 1.25 = 1.25 \]
So,
\[ h = 1.25 \quad \text{and} \quad s = 1.25 \]
Therefore, the costs are:
\[ h = $1.25 \] \[ s = $1.25 \]